Surgical ciliated cyst developing after Le Fort I osteotomy: Case report and review of the literature. Issue 6 (November 2019) - Tanio, Shunsuke; Tamura, Takayuki; Kasuya, Hiroshi; Kawasaki, Makoto; Taniguchi, Naomi; Otsuki, Kazuma; Fujii, Nobuyuki; Kodani, Isamu
Abstract: A surgical ciliated cyst, also referred as a locally aggressive lesion, stems from a prior surgery several years later as a delayed complication. It is reported that the cyst develops after orthognathic surgery. A 25-year-old man who had undergone Le Fort I osteotomy and bilateral intraoral vertical osteotomy of the mandible as treatment for jaw deformities in 2013 was referred to our hospital because of a swelling on the right side of the hard palate. Radiography and cone-beam computed tomography examinations revealed a unilocular cystic lesion in the right maxillary alveolus. All the teeth in the maxillary right quadrant were vital to electric pulp testing. Aspiration with an 18-gauge needle extracted rust-colored mucoid fluid. The lesion was diagnosed to be a maxillary cyst. Under general anesthesia, we removed the osteotomy fixation plates and excised the lesion. Histopathological examination revealed a cyst comprising cellular fibrous connective tissue, mainly lined by stratified squamous epithelium; however, the regions of focal pseudostratified columnar and ciliated epithelium were also present. Surgical ciliated cyst was diagnosed on the basis of histopathological, clinical, and radiographical findings. Although surgical ciliated cysts have sparsely been reported after orthognathic surgery, an increased awareness of such possibility is required to avoid delays in diagnosis. This lesion should always be a part of differential diagnosis of symptomatic patients who, in the past, have undergone antral or maxillary orthognathic surgery.